Clinical Presentation and Laboratory Features in Pediatric Typhoid Fever Patient Susceptibility to First-line Antibiotic Therapy - Dewi Ratnasari; Djatnika Setiabudi; Lulu Eva Rakhmilla (Althea Medical Journal, 2015)
Background: RTyphoid fever remainsa serious health problem in the world. The main cause of this disease is Salmonella enterica serovar Typhi. These microbes have developed resistance to first-line antibiotics (chloramphenicol, ampicillin, and co-trimoksazol) since 1950. Clinical presentation and laboratory features conducted in children infected with resistant strains tend to be more severe. The objective of this study was to determine the differences of clinical presentation and laboratory features in pediatric typhoid fever patient susceptibility to first-line antibiotics.Methods: This was an analytical cross-sectional study of total 119 typhoid fever children with positive blood culture of Salmonella Typhi based on medical data in Department of Child Health Dr. Hasan Sadikin General Hospital, Bandung during 2008–2012. Inclusion criteria included 76 patients with age range 1–15 years old, given an antibiotic, and had susceptibility test done. Numerical variable was the duration of fever in patients after given an antibiotic. Categorical variable included hepatomegaly, diarrhea, platelet count at admission, and leukocyte count at admission. Data were analyzed using a Mann-Whitney and Chi-square test.Results: There was no statistically significant difference in the duration of fever, leucocyte count at admission, and thrombocyte count at admission between sensitive and resistant response to chloramphenicol, ampicillin, and co-trimoksazol (p>0.05). Leucocyte count at admission in children with sensitive and resistant strain to ampicillin almost showed a difference (p=0.07) but still not statistically significant difference.Conclusions: There is no difference of clinical presentation and laboratory features in pediatric typhoid fever patient susceptible to first-line antibiotics. [AMJ.2015;2(4):584–90] DOI: 10.15850/amj.v2n4.653